(untitled) (The Review of Diabetic Studies, 2025)
Background: Lower respiratory tract infections (LRTIs) are a major cause of morbidity in children. Accurate, radiation-free diagnostic tools are essential for optimal care. This study aimed to compare the diagnostic efficacy of chest ultrasound (CUS) and chest X-ray (CXR) in pediatric patients with suspected LRTIs. Methods: This prospective cross-sectional study was conducted at Al-Azhar University Hospital, Assiut, Egypt, and included 172 pediatric patients. Each child underwent both CUS and CXR within 24 hours of clinical presentation. The sensitivity, specificity, interobserver agreement, and diagnostic accuracy of CUS and CXR were compared. Results: CUS showed higher sensitivity for detecting pulmonary consolidation (90%) and pleural effusion (85%) compared to CXR (78% and 65%, respectively). CUS also demonstrated superior specificity, interobserver agreement (κ = 0.89), and diagnostic accuracy (AUC = 0.90) compared to CXR (κ = 0.78, AUC = 0.78). Conclusions: CUS is a reliable, non-invasive, and radiation-free imaging modality that offers superior diagnostic accuracy over CXR in the initial evaluation of children with suspected LRTIs. These results support its use in clinical practice.